Analisis Hubungan Antara Personality Auditor Intern, Profesionalisme Auditor Internal, Hasil Kerja Auditor Intern dan Kinerja Lembaga Keuangan Mikro Syari'ah - Rahman El Junusi (Jurnal Ilmiah Aset, 2008)
A classic problem which has been always faced by the managements of shariah financial instution, in this case Baitul Mal Wat Tamwil (BMT), namely the limitation of human resources in terns of quality, including their internal auditor is able to influence the performance of shariah financial institutions because an internal auditor is responsible for provoding analysis, information, financial evaluation services, even for giving recommendations to the management. The goals of this research were to find out the characteristic of the variables of the research, namely: internal auditor’s work result, and shariah financial institution’s performance. Methodologies of research used in this research were first, the population, in were 11 BMTs grouped as City Forum BMTs, while the units of analysis were internal auditors and the heads or managers of BMTs. Second, samples were taken by using census method. Third, data collection technique used were questionenaires, interview, and documentation, fourth,descriptive quantitative technique and non paramateric statistical test of Kendall’s Tau were used to answer the goal research. The results of the research showed that (1) as regards the variable of internal auditor’s personality, formal education indicator could not explain internal auditor’s personality, asregards the variable of internal auditor’s professionalism, professional social responsibility indicator was the strongest indicator in explaining internal auditor’s professionalism, as regards internal auditor’a work results, management’s commitment indocator is the strongest indicator in explaining internal auditor’s work result and as efficiency is two strongest indicators in explaining shariah financial institution’s (BMT) performance, and (2) internal auditro’s personality, internal auditor’s professionalism, internal auditor’s professionalism, positive and significant correlation, which meant that the better the auditor internal’s personality the more professional the internal auditor, the more professional the internal auditor the better the work result, the better the work result the better shariah financial institution’s (BMT) performance.